The Effect of Play-Based Training on Volleyball Smash Skills at Kaur Public Elementary School No. 27 - Novia Jumanti; Megi Personi; Asnawati Asnawati (Educative Sportive, 2026)
This study aims to determine the effect of game-based training on the volleyball smash skills of fifth- and sixth-grade students at SD Negeri 27 Kaur. The study was motivated by the students’ low smash skills, which necessitated an effective training method suited to the characteristics of elementary school students. The method used was an experiment with a one-group pretest-posttest design. The study population consisted of 17 fifth- and sixth-grade students at SD Negeri 27 Kaur. Total sampling was used, meaning the entire population was included in the study. The instrument used was a volleyball smash skill test administered before (pretest) and after the intervention (posttest). Data analysis was conducted using normality tests, homogeneity tests, and t-tests. The results showed an improvement in smash ability following the game-based training. The mean pretest score of 19.59 increased to 23.47 on the posttest, representing an increase of 3.88 points. The t-test results indicate that play-based training has a significant effect on improving students’ volleyball smash skills. Based on the research results, it can be concluded that play-based training has a positive and significant effect on the volleyball smash skills of fifth- and sixth-grade students at SD Negeri 27 Kaur. Thus, play-based training can be used as an effective alternative training method to improve volleyball smash skills among elementary school students.